1974
DOI: 10.1149/1.2401714
|View full text |Cite
|
Sign up to set email alerts
|

Fine Structure in the Optical Spectra of Divalent Europium in the Alkaline Earth Sulfates

Abstract: Fine structure has been observed in the fluorescence and excitation spectra of Eu +2 in CaSO4 and in the fluorescence spectrum of Eu +~ in BaN~g(SO4)2. The fine structure in the fluorescence of Eu +2 in CaSO4 is identified as a zero phonon line with many sharp phonon replicas. The fine structure in its excitation spectrum is due to the closely spaced energy levels in the excited state produced by a strong exchange interaction splitting of the 4f65d states. The fine structure in the fluorescence of Eu +2 in BaM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(58 citation statements)
references
References 8 publications
6
51
1
Order By: Relevance
“…There is a clear progression in a frequency of 75 cm-1, yielding S = 6 [35]. A rich vibrational structure corresponding to the Raman spectrum has been observed for C a S t 4 : Eu z ÷ (4f 7) at liquid helium temperatures [36,37]. There is not much doubt that a stiff surroundings of the rare-earth ion in the host lattice promotes the occurrence of vibrational structure, and decreases the Stokes shift and the coupling parameter S. This is directly related to the fact that in this case there will be a relatively small offset of the parabolae (Q~ -Qg) in the configurational coordinate model (Fig.…”
Section: --'mentioning
confidence: 85%
“…There is a clear progression in a frequency of 75 cm-1, yielding S = 6 [35]. A rich vibrational structure corresponding to the Raman spectrum has been observed for C a S t 4 : Eu z ÷ (4f 7) at liquid helium temperatures [36,37]. There is not much doubt that a stiff surroundings of the rare-earth ion in the host lattice promotes the occurrence of vibrational structure, and decreases the Stokes shift and the coupling parameter S. This is directly related to the fact that in this case there will be a relatively small offset of the parabolae (Q~ -Qg) in the configurational coordinate model (Fig.…”
Section: --'mentioning
confidence: 85%
“…They have found that the emission colour evolves from green for M = Mg to blue for M = Ca and to violet for M = Sr due to the decreasing Eu-Br distances during this series. An interesting fact in these compounds is the presence of a highly resolved fine structure in the excitation spectra that normally arises when the exchange interaction between the [Xe]4f 6 configuration and the 5d electron is very low [18]. This observation makes them extremely suitable for computational approaches and allows experimental verifications of theory.…”
Section: Slater-condon Parametersmentioning
confidence: 99%
“…To the best of our knowledge, no calculations of Gd 3+ 4 f 7 → 4 f 6 5d excitations were published. However, extensive studies have been performed on the isoelectronic Eu 2+ 4 f 7 → 4 f 6 5d excitations [39,40]. The respective Eu 2+ excitation spectrum [40] is quite similar to the Gd 3+ excitation spectrum.…”
Section: +mentioning
confidence: 99%